A cultural history of the Chinese language - Gu, Sharron (McFarland & Co., 2012)
"This cultural history of Chinese demonstrates that the language grew and responded to its music and visual expression in a manner very similar to contemporary English and other western languages. This study shows how language has expanded the scope of Chinese imagination and offers a glimpse into the future of younger languages throughout the world"--Provided by publisher.